PERAN KURIKULUM NASIONAL DALAM PEMBENTUKAN INTEGRITAS SISWA SEKOLAH DASAR MELALUI PENDIDIKAN KARAKTER - Sari, Ayu Permata; Risma, Risma; Sari, Cut Kumala (Universitas Negeri Medan, 2025)
Globalization that affects the national education system demands values to shape the character of the younger generation. This study uses a literature study method on five SINTA - indexed journals, it was found the character education in elementary schools is implemented through integrating values in learning, habituation in school culture, extracurricular activities, and Proyek Profil Pelajar Pancasila (P5). Although it shows progress, its implementation still faces challenges such as lack of consistency, minimal parental rolee, and limited teacher role models.This study offers an integrative models based on an adaptive and contextual national curriculum.